Організація самостійної роботи студентів при викладанні дисципліни «Менеджмент, управління конкурентоспроможністю, витратами та проектами» - Нестеренко, Світлана Анатоліївна; Нестеренко, Светлана Анатольевна; Nesterenko, Svitlana (My University, 2019)
UK: У статті розглядаються питання організації самостійної роботи студентів при вивченні дисципліни «Менеджмент, управління конкурентоспроможністю, витратами та проектами».Дослідженнями доведено, що при впровадженні у розробленої методики організації самостійної роботи студентів підвищиться рівень якості знань студентів, що сприятиме подальшій самостійності студентів при вивченні зазначеної дисципліни. EN: In the article the questions of organization of independent work of students are examined at the study of discipline «Management, management a competitiveness, charges and projects». It is well-proven researches, that the level of quality of knowledges of students will rise at introduction at the developed method of organization of independent work of students, that will be instrumental in subsequent independence of students at the study of the noted discipline.
Оrganization of independent work of students at teaching of discipline «Management, management competitiveness, charges and projects»
Keywords: самостійна робота; менеджмент; управління навчанням; студент; конкурентоспроможність; методика; independent work; management; student; competitiveness; method; studies